THE DIET AND FEEDING HABITS OF LEUCISCUS VORAX FISH IN THE MAIN OUTFALL DRAIN MIDDLE IRAQ - Kadhim J.L. Al- Zaidy; Giuliana Parisi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
A total of 58 Leuciscus vorax samples were collected from the Main Outfall Drain, inside the borders of the central Iraqi province of Al-Qadisiyah, throughout the extended period from the beginning of January to the end of December 2022. Several traditional fishing methods were adopted. The results indicated that the males ratio were 44.83% (26 individuals) of the total number, while the females were 55.17% (32 individuals), with the total gender ratio that was 1:1.23. Results indicated that the highest food activity was observed from August to November. The lowest was in February and December, at a level of 75. It was noted that the highest level of feed density was in October (14.71) and the lowest was in December (11). Fish ranked first in the overall importance of nutrients for L. vorax species during the study phases, with 52.97% for fish less than 20 cm long and 95.93% for individuals longer than 20 cm. The study concluded that L. vorax was predatory in its feeding behavior, with variations in food items consumed depending on the length of the fish.